Adaptive spatial window aggregation query processing algorithm in wireless sensor networks. (1st January 2014) - Liu, Liang; Qin, Xiaolin; Zheng, Guineng; Li, Bohan
Users of wireless sensor networks (WSNs) often submit spatial window aggregation queries to obtain the summary information about a local area in the monitored region. We propose an adaptive spatial window aggregation query processing algorithm called ASWAP in this paper. It divides the query area into several disjoint sub–regions. A cluster head node is elected in each sub–region which collects the sensory data of sensor nodes in it, uses the data collected to calculate the partial query result and sends it to the cluster head node of the next sub–region. While a cluster head node fails during the above process, a recovery area can be found in its corresponding sub–region in which any node can substitute the cluster head node to resume the process of query processing. Experimental results show that in most cases ASWAP outperforms the existing IWQE algorithm in terms of energy consumption and query success rate.